السنة التقريرية وآثارها الفقهية في باب العبادات والمعاملات -دراسة أصولية وفقهية - أنيس, نافع; بوذينة, اسماعيل (جامعة الوادي university of eloued, 2023)
"تناولت مذكرتنا هذه دراسة موضوع السنة التقريرية وآثارها الفقهية في باب العبادات والمعاملات دراسة أصولية فقهية . فماهي هي السنة التقريرية ؟ وماهي آثارها الفقهية في باب العبادات والمعاملات؟ حيث أبرزنا في ثنايا هذا الموضوع ذكر جملة من الآراء والأقوال الأصولية والفقهية في ماهية السنة التقريرية, وما له صلة بها من شروط وحجية. وكان هذا في الجانب النظري, وأما في الجانب التطبيقي فقد ذكرنا جملة من تقريراته صلى الله عليه وسلم في العبادات والمعاملات وذكرنا استنباطات واستدلالات العلماء منها على العمل بتقريراته صلى الله عليه وسلم في الأحكام الشرعية. ومن أهم ما توصلنا إليه من نتائج : 1. تقديم صورة شاملة لماهية السنة التقريرية وما يتعلق بها. 2. السنة التقريرية حجة ودليل شرعي في الأحكام. 3. تعدد صور تقريرات الرسول صلى الله عليه وسلم من قول, وفعل, واستبشار, وسكوت, ومدح. "Our memorandum dealt with the study of the topic of the declarative year and its jurisprudential effects in the chapter of worship and transactions, a fundamental jurisprudential study. What is the reporting sunnah? What are its jurisprudential implications in the field of worship and transactions? In the context of this topic, we highlighted a number of fundamentalist and jurisprudential opinions and sayings regarding the nature of the declarative Sunnah, and the conditions and validity related to it. This was on the theoretical side, and as for the applied side, we mentioned a number of his reports, may God’s prayers and peace be upon him, regarding acts of worship and transactions, and we mentioned the scholars’ deductions and inferences from them on acting according to his reports, may God’s prayers and peace be upon him, regarding legal rulings. Among the most important results we have achieved are: 1. Providing a comprehensive picture of what the reporting year is and what is related to it. 2. The declarative Sunnah is an argument and legal evidence in rulings. 3. There are many forms of the Messenger’s reports, may God bless him and grant him peace, from words, deeds, optimism, silence, and praise. "
مدكرة
Keywords: "السنة التقرير الفقه"; Sunnah- Report - Jurisprudence